Investigating the Effect of Internal Marketing on the Staffs’ Desire to Remain in the Organization (Case Study: Aria Sasol Petrochemical Company) - Askari (Ph. D), Ahmad; Fard, Mehdi Zohadi (IJRDO - Journal of Business Management, 2018)
The purpose of this study was to investigate the effect of internal marketing on the willingness of employees to remain in Aria Sasol Petrochemical Company. The statistical population of the study consisted of 925 employees from Aria Sasol Petrochemical Company. The calculated sample is based on Morgan’s table and Cochran’s formula, which includes 272 individuals who have been extracted by random sampling. The research tools in this research included two internal marketing standard questionnaires (Al Hawari et al., 2013) and the standard questionnaire of the desire to remain (Weiner and Imery, 1980). Validity of the questionnaires was based on expert opinion and Bartlett’s test. Validity coefficient of internal marketing questionnaire was 0/793 and the standard questionnaire of the desire to remain was 0/916. And their reliability is based on Cronbach’s alpha coefficient which was 0.799 for internal marketing questionnaire and 0.847 for the standard questionnaire of the desire to remain and indicated that the questionnaire is desirable. In this research, regression analysis was used to analyze the research hypotheses and Friedman test for ranking variables. The results of this research showed that the internal marketing dimensions have a positive and meaningful effect on employees’ durability in the Aria Sasol Petrochemical Company. Also, the component of education and development has more impact and then there are communication, employee empowerment and motivation.